Mycobacterium bovis identification by a molecular method from post-mortem inspected cattle obtained in abattoirs of Mato Grosso do Sul, Brazil - Araújo, Cristina Pires de [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Prince, Karina Andrade de [UNESP]; Jorge, Klaudia dos Santos Gonçalves; Osório, Ana Luiza Alves Rosa (Instituto Oswaldo Cruz, Ministério da Saúde, 2005)
The presence of Mycobacterium bovis in bovine carcasses with lesions suggestive of tuberculosis was evaluated. Seventy-two carcass samples were selected during slaughter inspection procedures in abattoirs in the state of Mato Grosso do Sul, Brazil. Seventeen (23.6%) of samples showed colonies suggestive of mycobacteria that were confirmed to be acid-fast bacilli by Ziehl-Neelsen staining. Polymerase chain reaction (PCR) using primers specific for M. bovis identified M. bovis in 13 (76.5%) isolates. The PCR-restriction enzyme pattern analysis using gene encoding for the 65-kDa protein and two restriction enzymes identified the remaining four isolates that were represented by two M. tuberculosis complex and two nontuberculous mycobacteria. The results are indicative of infection of slaughter cattle by M. bovis and other mycobacteria in the state of Mato Grosso do Sul.
Keywords: Mycobacterium bovis; nontuberculous mycobacteria; polymerase chain reaction; PCR- restriction enzyme pattern analysis; cattle; post-mortem inspection; abattoirs